(3GdRgQI GdeVjI aj GdCNHGQ GdbGSejI GdeNJUQI ef GdSjQI GdeWgQIs - (3YHO Gddg Hf Ydj GdeShQj GdNhdGfjs
(3ChdgG (B:s
(3GdMeO ddg GdPi LYd MH Cgd HjJ fHjg aQjVI Ydi cd EfSGf hLYdge GdOYGI Edi GdNjQGJ s
(3BNQgG (B:s
(3BNQg eHJhQ hChd GdehLhO efg bhdg (B: (3hcja jUM ai GdCPgGf TF EPG EMJGL GdfgGQ Edi Odjd , agh GdeJUa HLejd GdSQjI hMejO GdSjQI , hgh GdeDjO HGdJhajb s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3cJHJ GdYfGhjf HGdMeQI s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3GdfSNI HgG CQVg , JQeje s
Keywords: (3GdJGQjNs